Magnetically-induced alignment of graphene via Landau diamagnetism. (May 2018) - Tian, Bo; Lin, Weiyi; Zhuang, Pingping; Li, Junzhu; Shih, Tien-mo; Cai, Weiwei
Abstract: Maneuvering the alignment of graphene nanoplatelets has been regarded as a formidable challenge. Meanwhile, Landau diamagnetism (LDM), which is capable of inducing anti-magnetic forces, typifies an attractive maneuvering mechanism, but has not been applied in practice. Here we have experimentally discovered that the LDM prevails in graphene nanoplatelets, and have further taken advantage of this mechanism to accomplish the alignment of graphene nanoplatelets in the N -methyl-pyrrolidone solvent under an external nonzero-gradient magnetic field. During experiments, we manipulate orientation angles and rates of graphene nanoplatelets via adjusting strengths of magnetic fields, and confirm such nanoplatelets' behaviors by means of laser-light-transmittance variations of the graphene colloid. Based on aforementioned mechanisms and experiments, we further fabricate a type of colloidal-graphene anisotropic materials for optical, thermal, and electrical applications. Our findings help develop future capabilities of maneuvering graphene's alignments in order to manufacture novel graphene-based isotropic materials. Graphical abstract: Image 1